Technology and Contemporary Life
328 p.
Keywords: Nearly everyone agrees that life has changed in our technological society, whether the contrast is with earlier stages in Western culture or with non-Western cultures. "Modernization" is just one of various terms that have been applied to the process by which we have arrived at the peculiar lifestyle typical of our age; whatever the term for the process, almost all analysts agree in finding technology to be one of its key ingredients. This is the judgment of critics of all sorts - anthropologists, historians, literary figures, sociologists, theologians. Volume 4 in the Philosophy and Technology series brings the perspectives of philosophers to bear on the issue of characterizing contemporary life, mainly in high-technology societies. Some of the philosophers look at the issue directly. Others focus on work life - or on the living arrangements that surround or condition or offer refuge from work life in technological society. Still others reflect on particular technologies, especially biotechnology and computer technology, that are increasingly affecting both work and family life. There is also a paper on the nature of thinking in technologi cal praxis, along with two papers on whether it is appropriate to export this sort of thinking to Third World countries, and another paper on the issue of responsibility in technology - which would have fit better in volume 3 of the series, entitled Technology and Responsibility (1987). Finally, volume 4 closes with a broad-ranging bibliography that takes work and technology as its focus.